PENERAPAN STRATEGI PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPS DI SEKOLAH DASAR - Leli Lestari; Muhamad Azhar; Lena Lena (El Midad, 2020)
The purpose of this study is to improve student learning achievements in social studies on important figures of the national movement as material, with fifth grade students with the implementation of Think Pair Share. This type of research is Classroom Action Research using the Kurt Lewin model and carried out through three cycles. This research was conducted on 18 fifth grade students of SDN 01 Bermani Ilir Kepahiang Regency Bengkulu Province. Data collection techniques in this study were carried out by observation, test sheets and documentation. Based on the results of the study, it showed that student learning achievements in social studies on subject matter figures of the national movement increased in each cycle as evidenced in the pre cycle with an average value of 54.44 with a percentage of students' learning outcomes 22.22%. Improvement in the first cycle obtained an average value of 69.72 with a percentage of 72.22% student learning achievements. In cycle II an average value of 80.00 was obtained with a percentage of 80.89% learning achievements and an increase in cycle III with an average value of 88.89 with a 100% completeness percentage of student learning achievements which shows that all students have achieved grades above the KKM.